Overexpression of HMGA1 confers radioresistance by transactivating RAD51 in cholangiocarcinoma - Jianping Song; Donghai Cui; Jing Wang; Junchao Qin; Shourong Wang; Zixiang Wang; Xiangyu Zhai; Huan Ma; Delin Ma; Yanfeng Liu; Bin Jin; Zhaojian Liu (Cell Death Discovery, 2021)
Abstract Cholangiocarcinomas (CCAs) are rare but aggressive tumors of the bile ducts. CCAs are often diagnosed at an advanced stage and respond poorly to current conventional radiotherapy and chemotherapy. High mobility group A1 (HMGA1) is an architectural transcription factor that is overexpressed in multiple malignant tumors. In this study, we showed that the expression of HMGA1 is frequently elevated in CCAs and that the high expression of this gene is associated with a poor prognosis. Functionally, HMGA1 promotes CCA cell proliferation/invasion and xenograft tumor growth. Furthermore, HMGA1 transcriptionally activates RAD51 by binding to its promoter through two HMGA1 response elements. Notably, overexpression of HMGA1 promotes radioresistance whereas its knockdown causes radiosensitivity of CCA cells to X-ray irradiation. Moreover, rescue experiments reveal that inhibition of RAD51 reverses the effect of HMGA1 on radioresistance and proliferation/invasion. These findings suggest that HMGA1 functions as a novel regulator of RAD51 and confers radioresistance in cholangiocarcinoma.